Penguatan Kultur Literasi di Madrasah Berbasis Riset Melalui Optimalisasi Fungsi Perpustakaan di MTs Negeri 1 Kota Batu - Walid, Muhammad; Fitriah, Nurlaeli; Pusposari, Luthfiya Fathi (J-PAI: Jurnal Pendidikan Agama Islam, 2020)
Gerakan Literasi Sekolah (GLS) is one of the government programs in order to regain reading interest in students. The meaning of literacy today is not merely meaning not being able to read, more than that literacy is related to understanding and sensitivity in relating it to life. Therefore the development of literacy is not only on the aspects of students but also all the components that can support the growth of literacy culture. The purpose of this study was to strengthen the literacy culture that had previously been built but was not optimal. Through mentoring, it is hoped that the culture built can be further strengthened by optimizing the function of the library as a learning resource. This article was written based on field studies in the form of dedication conducted at MTs Negeri 1 Kota Batu using ABCD aproach. The findings from the results of this study are that the optimization of library functions through workshops and capacity building activities for the library division team (komica) enriches their capacity as library ambassadors so that students who are members of the comica team more freely contribute to socializing library functions to colleagues other students in the MTs Negeri 1 Batu neighborhood by utilizing the IT capacity they obtain from workshops and capacity building activities.Keyword. Library Function; Literacy Culture; Research Class.